تاثير التجارة الالكترونية في التجارة الدولية - سالم عمر; دوباخ رشيد (جامعة المسيلة, 2024)
The Impact of E-commerce on International Trade A Case Study of the External Bank BEA Objective: This study aims to analyze the impact of e-commerce and electronic payment methods on international trade operations through a case study of the External Bank BEA. Problem Statement: - How do e-commerce and electronic payment methods contribute to facilitating and enhancing international trade operations and expanding market scope? Hypotheses: - E-commerce contributes to facilitating international trade operations and expanding market scope. - Electronic payment methods play a crucial role in facilitating and succeeding e- commerce operations. - Electronic payment methods help accelerate international trade operations and reduce associated costs. Findings: - The first hypothesis was confirmed, as the results clearly showed that e-commerce significantly contributes to facilitating international trade operations and expanding market scope, opening up new and diverse opportunities for cross-border trade. - The second hypothesis was confirmed, as the results showed that the sample positively evaluates the impact of electronic payment methods in improving the speed and ease of online payments and enhancing trust in electronic transactions, which improves access to financial services and reduces financial risks. - The third hypothesis was confirmed, as the results showed that electronic payment methods help accelerate international trade operations and reduce associated costs, improving risk management efficiency, facilitating access to international financing, and enhancing trust between companies
Keywords: E-commerce; electronic payment methods; international trade; BEA